2005
DOI: 10.1111/j.1463-1318.2005.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified technique for parastomal hernia repair in patients with intractable stoma‐care problems

Abstract: The modified onlay technique using a large sheet of ePTFE prosthetic mesh is a feasible option for treatment of parastomal hernia recurrence. Possible advantages of the procedure include stoma preservation, strengthening of the abdominal wall, and a reduced risk of recurrence, contamination, fistulization, and bowel adhesions and erosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Recurrence rate range from 4 to 12 %, infection rates were low (4-4.5 %), and morbidity rates were low [53,55]. A review of the literature reveals that laparoscopic modified Sugarbaker and keyhole techniques have recurrence rates of 9.2 versus 19.7 % (range 0-19 and 2.8-46 %, respectively) and mean wound infection was similar with both techniques (3.5 vs. 3.6 %) (Table 2) [47,[51][52][53][54][55][56][57][58]. Mesh was removed in four modified Sugarbaker and 11 laparoscopic keyhole procedures.…”
Section: Laparoscopic Versus Openmentioning
confidence: 96%
See 1 more Smart Citation
“…Recurrence rate range from 4 to 12 %, infection rates were low (4-4.5 %), and morbidity rates were low [53,55]. A review of the literature reveals that laparoscopic modified Sugarbaker and keyhole techniques have recurrence rates of 9.2 versus 19.7 % (range 0-19 and 2.8-46 %, respectively) and mean wound infection was similar with both techniques (3.5 vs. 3.6 %) (Table 2) [47,[51][52][53][54][55][56][57][58]. Mesh was removed in four modified Sugarbaker and 11 laparoscopic keyhole procedures.…”
Section: Laparoscopic Versus Openmentioning
confidence: 96%
“…However, mesh-fascial overlap in their study was only 2-3 cm (which lacks the standard [5 cm guideline currently used in abdominal hernia repair). Several studies evaluating open keyhole technique have shown recurrence rates of 9.4-12.6 % [4,47], but mesh-related complications were seen in 20 % (mesh migration, severe adhesions [4]). The mechanism for recurrence with the keyhole technique may be through the central aperture and herniation through the mesh openings [16,41].…”
Section: Mesh Repair Of Parastomal Herniasmentioning
confidence: 99%
“…A retrospective review of 20 paracolostomy hernia repairs using the open Sugarbaker technique resulted in 5 % wound infection and 15 % recurrence rate [73]. An alternative intraperitoneal technique is the keyhole method in which a small hole corresponding to the size of the stoma is cut out of the mesh to enable the stoma to pass through while still covering the entirety of the fascial defect as described in van Sprundel's study [74]. A review of this study and three others resulted in an overall morbidity rate of 22 %, wound infection rate of 2.2 %, and a recurrent PH rate of 9.4 % [68].…”
Section: Operative Management Open Approachmentioning
confidence: 99%
“…2). [15][16][17][18] However, there is a risk of obstructing the enterostomy if a smaller keyhole is made and a risk of recurrence if the hole is larger. In a review of reported series, overall morbidity was 22.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes of different types of open parastomal hernia repair in studies with greater than or equal to 10 patients Data from Refs 15,17,[20][21][22][23][24][25][26][27][28]. …”
mentioning
confidence: 99%